2022
DOI: 10.1007/s11356-022-23562-z
|View full text |Cite
|
Sign up to set email alerts
|

Eucalyptus saponin- and sophorolipid-mediated desorption of polycyclic aromatic hydrocarbons from contaminated soil and sediment

Abstract: The potential for biosurfactant-mediated desorption of polyaromatic hydrocarbons (PAHs) was evaluated using PAH-spiked soil and sediment. PAH desorption behaviors and toxicity of novel saponin biosurfactant extracted from Eucalyptus camaldulensis leaves and sophoro-lipid biosurfactant were investigated. Their PAH desorption efficiencies were compared with rhamnolipid biosurfactant and the industrial-chemical surfactant, Tween 20. Based on the emulsification indices, the salt tolerance of surfactants up to 30 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Additionally, PAHs can selectively affect certain microorganisms, leading to the enrichment of degrading functional bacteria and a decrease in the abundance of sensitive bacteria [ 37 , 38 ]. Many PAH degradation intermediates may also possess higher biological toxicity [ 39 ]. For instance, Dai et al [ 26 ] reported that benzoanthraquinone, an intermediate product from the degradation of BaA, is toxic to a class of ammonia-oxidizing archaea, exerting a stronger inhibitory effect.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PAHs can selectively affect certain microorganisms, leading to the enrichment of degrading functional bacteria and a decrease in the abundance of sensitive bacteria [ 37 , 38 ]. Many PAH degradation intermediates may also possess higher biological toxicity [ 39 ]. For instance, Dai et al [ 26 ] reported that benzoanthraquinone, an intermediate product from the degradation of BaA, is toxic to a class of ammonia-oxidizing archaea, exerting a stronger inhibitory effect.…”
Section: Discussionmentioning
confidence: 99%
“…Not only sandy soils have been identified to have this phenomenon, but loam, clay and peat soils in both dry and humid climates have also been found to be affected. Furthermore, soil water repellency can lead to reduced water availability caused by the non-uniform water retention and flow and dry soil volume between the pathways of preferential channels (gravity-induced fingers), which is damaging to plants [44].…”
Section: Removal Of Agrochemicalsmentioning
confidence: 99%